AB0448 Drug Survival of A Patients Cohort with Chronic Inflammatory RHEUMATISM Treated with Abatacept. (10th June 2014) - Bello, S.; Fanizzi, R.; Rotondo, C.; Rinaldi, A.; Dinoia, L.; Lopriore, S.; Serafino, L.; Bonali, C.; Iannone, F.; Lapadula, G.
Abstract : Objectives: The persistence in therapy is an important assessment tool of therapy efficacy in patient with chronic disease. The aim of this study was to evaluate drug survival (DS) of a patients cohort suffering from chronic inflammatory rheumatism treated with abatacept. Methods: From September 2008 to March 2013, we retrospectively observed a total of 107 patients starting therapy with abatacept, in a single center of southern Italy. They were 88 females and 19 males, aged between 21 and 85 years (54.65) and with disease duration between 2 and 45 years (11, 71). 60 patients were suffering from rheumatoid arthritis (RA; 56.07%), 6 from chronic undifferentiated polyarthritis (5.60%), 2 from juvenile idiopathic arthritis (1.86%), 1 from Still's disease (0, 93%) and 38 (35.51%) from seronegative spondyloarthritis (SpA). 91.58% (98 patients) had also comorbidities. 18.69% of the patients (20 patients) were naive to the treatment with biological drugs. 77.00% of patients took DMARDs and 69, 39% were receiving steroid. Results: DS resulted averaging 15.40 months, retention rate after 1 year (RR1) was 49.53% and after 2 years (RR2) was 25.23%. Half of the patients (53 patients, 49.53%) interrupted the therapy during the observation period, mostly due to inefficacy or loss of efficacy (64.15%) and only 3.77% due to side effects. DS, RR1 and RR2 were clearly higher in patients taking DMARDs compared to patients taking abatacept in monotherapy (14.58 vs 11.26 months, p= ns; 50.64% vs 30.43%, p=0.038 and 24.67% vs 8.69%, p=0.042, respectively). The RA patients showed higher values of the examined parameters compared to the patients with SpA (DS: 17.31 vs 11.36 months, p=0.029; RR1: 53.33% vs 44.73%, p= ns; RR2: 33.33% vs 7.89%, p=0.0001). Considering patients in first-line vs patients in subsequent lines of biological therapy DS resulted 12.50 vs 16.06 months, RR1 45.60% vs 50.57% and RR2 20.00% vs 26.43%; this result could be justified by the shorter period of observation of patients in first-line of biological therapy, due to the more recent use of abatacept in patients naive to biological therapy. 80.00% of these patients resulted in fact still in therapy at the end of the observation vs 43.67% of the patients in subsequent lines of biological therapy (p=0.0001).The average value of DAS 28 and good or moderate EULAR response achievement appeared better in patients in first line of biological treatment (3.59 vs 4.04, p=ns and 63.16% vs. 46.57%, p=0.0228, respectively). Conclusions: Into a cohort of patients with chronic inflammatory rheumatism and treated with abatacept DS was in line with the results reported in few studies on the subject. The persistence in therapy was better in patients with RA compared to patients with SpA and in patients treated with DMARDs compared with patients taking abatacept in monotherapy. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2669